12 Reliability of Two-Person Anthropometric Measurement of Young Children with Parent Facilitator. (21st October 2022) - Rae, Sarah; Ong, Frank; Pullenayegum, Eleanor; Carsley, Sarah; Hamilton, Jill; Maguire, Jonathon; Dennis, Cindy-Lee; Birken, Catherine
Abstract: Background: Body Mass Index is recommended by the World Health Organization for the measurement of growth and the diagnosis of overweight and obesity in children. The reliability of anthropometric measurements is important for assessment of child growth due to the challenges faced when measuring younger children, including the difficulty of having the child remain still during measurement collection. The current gold-standard for anthropometric measurement collection in children in a clinical research setting, set by the World Health Organization, requires the use of two trained anthropometrists. Objectives: The purpose of this study was to determine the reliability of anthropometric measurements between two trained anthropometrists working in a pair and one trained anthropometrist working with a child's parent/caregiver in a primary healthcare setting. Design/Methods: An observational study to determine measurement reliability was conducted in a primary care child research network in Canada. 76 children 0 – 5 years old had their length/height, weight, head, arm, and waist circumference measured a total of four consecutive times: twice by two trained anthropometrists working in a pair (researcher-researcher team) and twice by one trained anthropometrist working with a child's parent/caregiver (researcher-parent team). Inter- and intra- observer reliability was calculated using the technical error of measurement (TEM), relative TEM (%TEM) and the coefficient of reliability (R). Results: The %TEM values across both age groups, children 0 - < 2 and 2 – 5 years of age, for length/height and weight were < 2% and the R coefficient values were >0.99, indicating a high degree of inter- and intra- observer reliability. The TEM values were greater for inter- and intra- observer reliability across all age groups for length/height in comparison to other anthropometric measurement parameters, with greater variation seen in the length for children 0 - < 2 years of age. The TEM values across both age groups for inter- and intra- observer reliability of arm circumference was outside of the acceptable range of < 2%, indicating greater measurement error. There was greater variation seen in waist circumference across both age groups. Conclusion: This study suggests that anthropometric measurement, including length/height and weight, taken by one trained anthropometrist with the assistance of a parent/caregiver is reliable. These findings can be used to encourage the utilization of a child's parent/caregiver to assist with anthropometric measurement collection in clinical setting(s) to enhance feasibility and efficiency and reduce the research costs of including a second trained anthropometrist.